Interpreting students’ perceptions in fluid mechanics learning outcomes - Soares, Filomena (2015)
The objective of this study is to analyse the impact of introducing a practical work in the learning process of the Fluid Transport Systems course in Chemical Engineering degree. The students, in groups of two or three elements, were free to choose the application case in order to develop the practical work proposed by the responsible teachers. The students selected a centrifugal pump to supply water to houses or buildings and designed the piping system. The practical work was evaluated through the written report. The students' perceptions were analysed through a questionnaire. The learning outcomes were also considered in order to understand how the fluid mechanics concepts were acquired. In the teachers' point of view the teamwork should enable the development of students' soft skills and competencies, promoting the ability to integrate and work in teams. The students changed their learning processing and perception becoming more reflective and less accommodative, forcing them to think critically and share opinions. Regarding the Fluid Mechanics assessment, the practical work increased, in average, the final grade at least one value.